2012
DOI: 10.1111/j.1476-5381.2012.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

1‐Dehydro‐[10]‐gingerdione from ginger inhibits IKKβ activity for NF‐κB activation and suppresses NF‐κB‐regulated expression of inflammatory genes

Abstract: BACKGROUND AND PURPOSEPungent constituents of ginger (Zingiber officinale) have beneficial effects on inflammatory pain and arthritic swelling. However, the molecular basis for these pharmacological properties is only partially understood. Here, we investigated the molecular target of 1-dehydro-[10]-gingerdione (D10G), one of the pungent constituents of ginger, that mediates its suppression of NF-kB-regulated expression of inflammatory genes linked to toll-like receptor (TLR)-mediated innate immunity. EXPERIME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 49 publications
3
47
0
3
Order By: Relevance
“…123 This latter effect on inflammatory cytokine activity may also be due to the discovery that ginger directly activates IKKβ, leading to reduced IkB phosphorylation in human macrophages treated with LPS. 124 . In whole animals, this effect was confirmed when mice given LPS showed reduced levels of IFN-γ and IL-6 in serum and reduced NFκB and COX2 expression with ginger treatment.…”
Section: Gingermentioning
confidence: 95%
“…123 This latter effect on inflammatory cytokine activity may also be due to the discovery that ginger directly activates IKKβ, leading to reduced IkB phosphorylation in human macrophages treated with LPS. 124 . In whole animals, this effect was confirmed when mice given LPS showed reduced levels of IFN-γ and IL-6 in serum and reduced NFκB and COX2 expression with ginger treatment.…”
Section: Gingermentioning
confidence: 95%
“…Another study revealed that ginger suppresses expression of inflammatory genes in a NF-κB dependent manner [26]. NF-κB is a main transcription factor down-stream of TLR2 and 4 and participates in the expression of the TLRs [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Os TLRs quando ativados, transmitem cascatas de sinais que culminam na fosforilação do IkBα catalisado por IKKB, dando origem ao fator de transcrição kappa B (NF-kB), um potente indutor da transcrição de genes de citocinas pró-inflamatórias (RULAND; MAK, 2003). Lee et al (2012) demonstraram que IKKB é alvo molecular do composto 1-Dehydro-[10]-gingerdione (D10G), bloqueando sua ação catalítica e consequentemente suprimindo a expressão de NF-KB.…”
Section: Efeito Antagônico Do Gengibre Sobre O Lpsunclassified